A Relational Database of WHO Mortality Data Prepared to Facilitate Global Mortality Research. (30th September 2015) - de Roos, Albert
Detailed world mortality data such as collected by the World Health Organization gives a wealth of information about causes of death worldwide over a time span of 60 year. However, the raw mortality data in text format as provided by the WHO is not directly suitable for systematic research and data mining. In this Data Paper, a relational database is presented that is created from the raw WHO mortality data set and includes mortality rates, an ICD-code table and country reference data. This enriched database, as a corpus of global mortality data, can be readily imported in relational databases but can also function as the data source for other types of databases. The use of this database can therefore greatly facilitate global epidemiological research that may provide new clues to genetic or environmental factors in the origins of diseases.